2011
DOI: 10.1113/jphysiol.2010.199018
|View full text |Cite
|
Sign up to set email alerts
|

In vivo stimulation of oestrogen receptor α increases insulin‐stimulated skeletal muscle glucose uptake

Abstract: Non-technical summary Previous studies show that oestrogen is beneficial for maintaining blood glucose levels and helping the body respond to insulin. Despite these previous findings, the mechanism by which oestrogen acts is unknown. We show that specific activation of oestrogen receptor α (ERα) increases glucose uptake into skeletal muscle when insulin is present. Activation of oestrogen receptor β (ERβ) alone or activation of both ERα and ERβ together did not increase glucose uptake into skeletal muscle. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 65 publications
(162 reference statements)
2
80
1
2
Order By: Relevance
“…E 2 exerts an anti-atherogenic effect influencing lipolysis and lipogenesis thus reducing the concentration of lipids in both the blood (Shi et al 2013) and tissues (Hewitt et al 2004, Jelenik, Roden 2013. Moreover, E 2 might decrease synthesis and increase FFA oxidation during hyperinsulinemia (Musatov et al 2007, Gorres et al 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E 2 exerts an anti-atherogenic effect influencing lipolysis and lipogenesis thus reducing the concentration of lipids in both the blood (Shi et al 2013) and tissues (Hewitt et al 2004, Jelenik, Roden 2013. Moreover, E 2 might decrease synthesis and increase FFA oxidation during hyperinsulinemia (Musatov et al 2007, Gorres et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…E 2 exerts beneficial effects on the cardiovascular system by reducing nuclear factor kappa-B (NFkB), IkB and iNOS expression during ischemia (Karpuzoglu, Ahmed 2006). Under normal conditions, E 2 also influences energy usage by regulating GLUT and CD36 in heart (Gorres et al 2011, Tepavcevic et al 2011.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…41 Other possibilities include increased ERa expression after TBI 32 and an increase in the neurological score by lowering intracranial pressure. 28,41 Furthermore, the increase in progesterone and progesterone receptor levels 16 may mimic the effects of PPT and estrogen on VCS score. This increase in progesterone and progesterone receptor levels may be sufficient to mimic the effects of PPT and estrogen on VCS score.…”
mentioning
confidence: 99%
“…Previous studies showed that an ovariectomy procedure in rats caused hypertriglyceridemia (Hassan et al 2013) and, in a human study, circulating TG concentrations were higher in postmenopausal than pre-menopausal women (Furusyo et al 2013). Additionally, an estrogen injection prevented TG accumulation in liver and muscle of ovariectomized (OVX) mice by reducing fatty acid synthesis, increasing b-oxidation by down-regulating ACC1 and FAS, and up-regulating AMPK (D'Eon et al 2005;Gorres et al 2011). However, the effects of E 2 are unknown in regard to hepatic TG synthesis.…”
Section: Introductionmentioning
confidence: 99%